1995
DOI: 10.1161/01.cir.91.10.2520
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Coagulation and Fibrinolytic and Kallikrein-Kinin Systems in the Acute and Postacute Phases in Patients With Unstable Angina Pectoris

Abstract: Our data indicate that in patients with unstable angina pectoris, intracoronary thrombus formation is associated with a hypercoagulative state, including activation of the contact phase and of the kallikrein system and increased bradykinin generation. The persistence of this hypercoagulative state, together with a disturbed fibrinolysis, might indicate an increased risk for further coronary events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
57
1
3

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(69 citation statements)
references
References 42 publications
8
57
1
3
Order By: Relevance
“…A level of >500 mg/L had an independent diagnostic value for myocardial infarction and increased the diagnostic sensitivity of the electrocardiogram and history from 73% to 92%. Hoffmeister et al [14] investigated the coagulation profile in UAP and demonstrated a persistently strong trend of elevated D-dimer levels during the first 10 days after admission. Accordingly, Oldgren et al [15] showed that on longterm follow-up (median 29 months) of patients with UAP, higher baseline levels of D-dimer were correlated with increased mortality.…”
Section: Discussionmentioning
confidence: 99%
“…A level of >500 mg/L had an independent diagnostic value for myocardial infarction and increased the diagnostic sensitivity of the electrocardiogram and history from 73% to 92%. Hoffmeister et al [14] investigated the coagulation profile in UAP and demonstrated a persistently strong trend of elevated D-dimer levels during the first 10 days after admission. Accordingly, Oldgren et al [15] showed that on longterm follow-up (median 29 months) of patients with UAP, higher baseline levels of D-dimer were correlated with increased mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrinopeptide A, which reflects thrombin activity, has been analysed in similar studies and may, despite the risk of venipuncture-procedure related variations, allow a more reliable comparison between heparin and a direct thrombin inhibitor [19,[27][28][29][30][31] . Markers for thrombin activity have been shown to increase in patients with unstable coronary artery disease in comparison to control patients or healthy individuals [31][32][33] . In a study by Merlini et al 32 , with up to 6 months of follow-up, a prolonged hypercoagulable state with sustained high levels of prothrombin fragments 1 and 2 was reported.…”
Section: Discussionmentioning
confidence: 99%
“…No such elevation was observed for fibrinopeptide A in the studies by Merlini et al, suggesting that thrombin activity, but not generation, returns to normal levels after the onset of the disease. In the present study, we used ELISA assays for the analysis of prothrombin fragments 1 and 2 and thrombin-antithrombin, which are well established and utilized in trials with similar patient categories [16,17,19,33,34] . Results from previous studies on thrombin inhibitors for unstable coronary artery disease are not totally consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…12 Typical procoagulant abnormalities in ACS are increased circulating thrombin marker levels, such as prothrombin fragment 1.2 (F1.2) or thrombin-antithrombin complexes (TAT), with the maximum values seen in subjects with ST-elevation myocardial infarction (STEMI) and markedly elevated cardiac troponin levels, a marker of myocardial necrosis. [13][14][15][16][17] Moreover, enhanced thrombin activity toward fibrinogen within 12 hours of acute myocardial infarction (AMI) has been found to identify patients at an increased risk of cardiac mortality. 18 Patients with ACS who developed in-hospital recurrent ischemia despite at least 72 hours of heparin infusion had significantly higher plasma levels of thrombin markers determined before the coronary event, and heparin was only partially able to antagonize thrombin activity.…”
mentioning
confidence: 99%